Rancang Bangun Website Gereja Imanuel Mandomai Menggunakan Php Mysql - Maria, Firda Kristeni; Kristianti, Novera (Journal of Information Technology and Computer Science, 2023)
Imanuel Mandomai Church is the oldest church located in Mandomai village, West Kapuas district. This church does not have a website yet. So that this Church in its pursuit of information is still focused only on the church area, so if we want to know information in the church then we have to come directly to the church, of course this is very offensive if we need this information quickly and suddenly. Based on this background, the Imanuel Mandomai Church Design Website was created so that this Church can be known by the public and the community can also get information from the website. The methodology used in designing and building this website is the waterfall method, namely analysis, design, implementation and testing. The design is using Data Flow Diagrams (DFD) using context diagrams, DFD Levels 1 and 2, Flowcharts, Entity Relationships (ERD), as well as coding using PHP and MySQL and Blackbox as software testing methods.